Caesarean Section Rate and Frequencies of Indications Using Robson-Ten Classifications - Sadia Ali; Shazia Khattak; Rabeea Sadaf; Shamshad Begum; Nasreen Kishwar (Gandhara University, 2021)
OBJECTIVES: To determine the caesarean section rate (CSR) and frequency of different indications of caesarean section (CS) in a tertiary care hospital. METHODOLOGY: A retrospective study done in the Department of Obstetrics and Gynecology Hayatabad Medical Complex Hospital Peshawar, a tertiary care hospital, from a period of 1st January 2019 till 31st December 2019. The required data was collected from the patient's hospital records (clinical charts) with the consent of the hospital ethical committee. RESULTS: The total number of deliveries over the study period was 5611. Out of these 1258 patients were delivered through caesarean section (CS), giving a CSR of 22%. The main contributing groups in our study were Robson Groups R5 (multiparous with prior CS, singleton, cephalic and >37 weeks), R1 (nulliparous, cephalic, singleton >37 weeks in spontaneous labor or CS) and R6 (all nulliparous breeches) with percentages of 21.1%, 17.5% and 12.9% respectively. CONCLUSION: Our study showed Robson Groups 5, 2 and 6 as the major contributors, focusing on these groups could have an impact on decreasing the cesarean section rate in future. Limiting the primary cesarean section rate can affect the overall cesarean section rate (CSR).